Political discourse in Malaysian blogs / Zanariah Jano, Siti Rohana Omar dan Norun Najjah Ahmat - Jano, Zanariah; Omar, Siti Rohana; Ahmat, Norun Najjah (2008)
This study is intended to examine political discourse in a sample of Malaysian Blogs, which operate largely outside the system of close government supervision and monitoring of media content. This paper analyzes blogs quantitatively in terms of freedom of expression, propaganda and compares blog content to analogous samples of content from mainstream newspapers in Malaysia in the midst of 2008 election. The study has revealed that blogging has developed new arena for political discussion, given voice to more criticism of policies, and weakened state control over political discourse.